أثر غياب الدفع الإلكتروني عبر الإنترنت عمى ديناميكية الاقتصاد الوطني الجزائري -دراسة حالة قطاع السياحة - بن ذهيبة محمد بن ذهيبة محمد; قدري صلاح الدين قدري صلاح الدين (Finance and Business Economies Review, 2017)
<span dir="ltr" style="left: calc(var(–scale-factor)*61.46px); top: calc(var(–scale-factor)*429.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.992308);" role="presentation">The Information and communication technology is one of the most used in the tourism industry. It <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925048);" role="presentation">greatly <span dir="ltr" style="left: calc(var(–scale-factor)*87.69px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90852);" role="presentation">contributes <span dir="ltr" style="left: calc(var(–scale-factor)*138.29px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932477);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*152.43px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*170.90px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99316);" role="presentation">int<span dir="ltr" style="left: calc(var(–scale-factor)*181.49px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907743);" role="presentation">egration <span dir="ltr" style="left: calc(var(–scale-factor)*220.46px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*235.08px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*253.55px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950207);" role="presentation">Algerian <span dir="ltr" style="left: calc(var(–scale-factor)*294.58px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931043);" role="presentation">tourism <span dir="ltr" style="left: calc(var(–scale-factor)*331.15px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907522);" role="presentation">destination <span dir="ltr" style="left: calc(var(–scale-factor)*381.17px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*401.91px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.864839);" role="presentation">enhancement <span dir="ltr" style="left: calc(var(–scale-factor)*460.47px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*475.21px); top: calc(var(–scale-factor)*442.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945);" role="presentation">its <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*455.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971922);" role="presentation">opportunities in the international markets, and has enabled this destination to create a direct link with <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*469.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895973);" role="presentation">internaute. <span dir="ltr" style="left: calc(var(–scale-factor)*98.66px); top: calc(var(–scale-factor)*469.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.03609);" role="presentation">This study aims to identify the use of e-<span dir="ltr" style="left: calc(var(–scale-factor)*277.61px); top: calc(var(–scale-factor)*469.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.98789);" role="presentation">Commerce as a tool to increas<span dir="ltr" style="left: calc(var(–scale-factor)*411.22px); top: calc(var(–scale-factor)*469.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01412);" role="presentation">e the capacity of <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*482.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921969);" role="presentation">enterprises in the product good and service development, increase market share through better promotion <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*495.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940084);" role="presentation">of the product, improve the communication quality, and the quality of information, and finally improve the <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*508.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934258);" role="presentation">quality of destination imag<span dir="ltr" style="left: calc(var(–scale-factor)*161.54px); top: calc(var(–scale-factor)*508.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907249);" role="presentation">e. In the ended, the study found that there is a relationship between the use of e- <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*521.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906673);" role="presentation">commerce as a tool to expand the potential foreign market of the <span dir="ltr" style="left: calc(var(–scale-factor)*314.95px); top: calc(var(–scale-factor)*521.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927253);" role="presentation">Algerian destination.